Analysis Of Preservatives in Jelly at Traditional Markets: Analisis Pengawet pada Jelly Agar di Pasar Tradisional - Dinar Wahyu Utami; Petrus Darmawan (Program Studi S1 Teknik Kimia, Fakultas Teknik, Universitas Setia Budi, 2020)
Jelly is a processed food product from seaweed that is given fruit juice, sugar and water and has a semi-solid but chewy texture. Jelly producers add food preservatives to maintain quality and extend shelf life. Permitted preservatives and commonly used for jelly products are sodium benzoate, potassium sorbate and sulfur dioxide. Each preservative is regulated the maximum limit of its use in the Head of BPOM RI Regulation No. 36 of 2013. This study aims to determine the content and levels of preservatives contained in jelly products.Qualitative analysis was carried out on preservatives of sodium benzoate, potassium sorbate and sulfur dioxide whether found in jelly products sold in traditional markets in the District of Jebres, Surakarta. Furthermore, quantitative analysis was carried out to determine the levels of preservatives contained in jelly agar products. Quantitative analysis of preservatives in jelly products by titrimetry and HPLC methods.The results showed that of the four jelly samples analyzed, there were three positive jelly samples containing sodium benzoate preservative with each Jelly A level of 688,559 mg / kg; Jelly B is 488,161 mg / kg and Jelly C is 139,711 mg / kg. There are 2 samples of jelly that do not meet the quality standards according to the Head of BPOM RI Regulation No. 36 of 2013 ie samples of Jelly A and Jelly B because more than 200 mg / kg. Abstrak Jelly agar merupakan produk olahan pangan dari rumput laut yang diberi sari buah-buahan, gula dan air serta memiliki tekstur setengah padat namun kenyal. Produsen jelly agar menambahkan bahan pengawet makanan untuk mempertahankan kualitas dan memperpanjang umur simpan. Bahan pengawet yang diperkenankan dan biasa digunakan untuk produk jelly agar adalah natrium benzoat, kalium sorbat dan belerang dioksida. Masing-masing bahan pengawet tersebut diatur batas maksimum penggunaannya dalam Peraturan Kepala BPOM RI No. 36 Tahun 2013. Penelitian ini bertujuan untuk mengetahui kandungan dan kadar pengawet yang terdapat pada produk jelly agar. Analisis kualitatif dilakukan terhadap bahan pengawet natrium benzoat, kalium sorbat dan belerang dioksida apakah terdapat pada produk jelly agar yang dijual di pasar tradisional di Kecamatan Jebres, Surakarta. Selanjutnya dilakukan analisis kuantitatif untuk mengetahui kadar bahan pengawet yang positif terdapat pada produk jelly agar. Analisis kuantitatif bahan pengawet pada produk jelly agar dengan metode titirimetri dan HPLC. Hasil penelitian menunjukkan dari keempat sampel jelly agar yang dianalisis, terdapat tiga sampel jelly agar yang positif mengandung bahan pengawet natrium benzoat dengan kadar masing-masing Jelly A sebesar 688,559 mg/kg; Jelly B sebesar 488,161 mg/kg dan Jelly C sebesar 139,711 mg/kg. Terdapat 2 sampel jelly agar yang tidak memenuhi baku mutu sesuai Peraturan Kepala BPOM RI No. 36 Tahun 2013 yaitu sampel Jelly A dan Jelly B karena lebih dari 200 mg/kg.